COMPARISON (CONTRAST) AS A LINGUISTIC PHENOMENON - Umurkulov Zafar Bekpulatovich (Scholar Express Journal, 2024)
Through expressions formed on the basis of a comparison (contrast) attitude, a person realizes himself, feels the world, the connection that he perceives in things-phenomena. The article expresses opinions on the peculiarities of comparison as a linguistic phenomenon
Keywords: comparison; equalization; analogy; comparative character